2015
DOI: 10.1186/s13104-015-0998-y
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary spinal cord metastasis of cholangiocarcinoma: a case report

Abstract: BackgroundCholangiocarcinomas are rare tumors, and metastasis to the intramedullary spinal cord is also rare. To the best of our knowledge, this is the first case of simultaneous cholangiocarcinoma and intramedullary spinal cord metastasis to be described in the medical literature.Case presentationA 62-year-old Caucasian male with a cholangiocarcinoma presented pain around his left shoulder without any other symptoms. The results by magnetic resonance imaging and F18 fluorodeoxyglucose positron emission tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Other sources argue that the increasing incidence of these less common metastatic sites may be attributable to an increase in overall survival of patients secondary to the advent of multimodal therapies. 3 This increase in incidence is supported by studies from 2010 and 2013 6,33 that correlated prolonged overall survival and progression-free survival with modern management strategies, particularly the use of cisplatin and gemcitabine in palliative situations. This theory is supported by the fact that 6 patients, including our own, had prolonged latency periods between the original presentation of CCC and metastasis to the spine and/or cranium.…”
Section: Figure 3 Histopathology Hematoxylin and Eosin Stains Of Thementioning
confidence: 96%
See 3 more Smart Citations
“…Other sources argue that the increasing incidence of these less common metastatic sites may be attributable to an increase in overall survival of patients secondary to the advent of multimodal therapies. 3 This increase in incidence is supported by studies from 2010 and 2013 6,33 that correlated prolonged overall survival and progression-free survival with modern management strategies, particularly the use of cisplatin and gemcitabine in palliative situations. This theory is supported by the fact that 6 patients, including our own, had prolonged latency periods between the original presentation of CCC and metastasis to the spine and/or cranium.…”
Section: Figure 3 Histopathology Hematoxylin and Eosin Stains Of Thementioning
confidence: 96%
“…10 Radiotherapy with or without chemotherapy was found to provide pain relief in up to 90% of patients with symptoms of short duration. 36 Chemotherapy and hormonal therapy are considered to be the least effective treatments overall 3,5,6,10 ; however, in studies from 2011 and 2017, the use of gemcitabine and cisplatin together demonstrated positive effects on systemic lesions and potential clinical improvement. 28,37 As mentioned previously, the use of Whipple duodenopancreatectomy in extrahepatic CCC has increased the overall 5-year survival rate from 12% to 28% in local disease.…”
Section: Figure 3 Histopathology Hematoxylin and Eosin Stains Of Thementioning
confidence: 99%
See 2 more Smart Citations
“…The increased incidence of biliary cancers is increasing, likely due in part to the improvements in the performance of laparoscopic cholecystectomies which can find these cancers incidentally (13)(14)(15)(16)(17)(18). Similarly, the incidence of biliary cancer metastasis to the brain or CNS is increasing in the setting of improved management of these diseases with increased survival time, which prolongs the time during which such a metastasis may occur (5,19). In this retrospective study, we evaluated all occurrences of brain metastases originating from primary biliary cancers with cases derived from three databases, two databases focused on all patients with biliary cancer, only a subset of whom developed brain metastases (UCSF from 1990 to 2020), and one database focused on all patients with brain metastases, only a subset of whom have biliary cancer (Stanford 2008 to 2018).…”
Section: Introductionmentioning
confidence: 99%